Genetic variants in the Fat and Obesity Associated (FTO) gene and risk of Alzheimer's disease. - Christiane Reitz; Giuseppe Tosto; Richard Mayeux; Jose A Luchsinger; NIA-LOAD/NCRAD Family Study Group; Alzheimer's Disease Neuroimaging Initiative (PLoS ONE)
Background Recent studies showed that polymorphisms in the Fat and Obesity-Associated (FTO) gene have robust effects on obesity, obesity-related traits and endophenotypes associated with Alzheimer's disease (AD). Methods We used 1,877 Caucasian cases and controls from the NIA-LOAD study and 1,093 Caribbean Hispanics to further explore the association of FTO with AD. Using logistic regression, we assessed 42 SNPs in introns 1 and 2, the region previously reported to be associated with AD endophenotypes, which had been derived by genome-wide screenings. In addition, we performed gene expression analyses of neuropathologically confirmed AD cases and controls of two independent datasets (19 AD cases, 10 controls; 176 AD cases, 188 controls) using within- and between-group factors ANOVA of log(10) transformed rank invariant normalized expression data. Results In the NIALOAD study, one SNP was significantly associated with AD and three additional markers were close to significance (rs6499640, rs10852521, rs16945088, rs8044769, FDR p-value: 0.05<p<0.09). Two of the SNPs are in strong LD (D'>0.9) with the previously reported SNPs. In the Caribbean Hispanic dataset, we identified three SNPs (rs17219084, rs11075996, rs11075997, FDR p-value: 0.009<p<0.01) that were associated with AD. These results were confirmed by haplotype analyses and in a metaanalysis in which we included the ADNI dataset. FTO had a significantly lower expresssion in AD cases compared to controls in two independent datasets derived from human cortex and amygdala tissue, respectively (p = 2.18 × 10-5 and p<0.0001). Conclusions Our data support the notion that genetic variation in Introns 1 and 2 of the FTO gene may contribute to AD risk.